KONFLIK HARTA PUSAKA ANTAR SUKU DI NAGARI TAMBANGAN KECAMATAN X KOTO KABUPATEN TANAH DATARâ (STUDI KASUS KONFLIK ANTAR KEMENAKAN MALAKOK SUKU PISANG DENGAN PIHAK SUKU PANYALAI) - Putri, Dwiyuliana; Adiyalmon, Adiyalmon; Syafrini, Delmira (Pendidikan Sosiologi, 2014)
Dwiyuliana Putri (NIM:09070248), Thesis title, Konflik Harta Pusaka Antar Suku di Nagari Tambangan Kecamatan X Koto Kabupaten Tanah Datar (Studi Kasus: Kemenakan Malakok Suku Pisang dengan Pihak Suku Panyalai), Thesis, Sociology Education Program (STKIP) PGRI West Sumatera, Padang, 2014.The thesis explains about a conflict of inheritance among tribes in Nagari Tambangan which occurred between Anak Kemenakan Malakok[1] from tribe of Pisang[2] and tribe of Panyalai[3]. There are many efforts tried to so lve the problem but it is still incomplete yet. The aims of the research are 1) to explain and to analize the causes of the inheritance conflict. 2) what makes the conflict still incomplete. The theory used is conflict theory by Lewis A. Coser. For method of research, the researcher uses qualitative approach with using a case study of research. The informants, 20 people, are taken through snowball sampling. Data found, which are primary and secondary data form, are collected through interviewing, observing, and cocumentation with using supporting isntruments like pen, handphone, etc. Analysis unit of the research is group. The result of this research reveal that 1. The main inheritance conflict which happen between Kemenakan Malalkok from tribe of Pisang and panyalai tribe. a) The grab of the authority of the farm management, b) the construction of a house which is in the confilct farm, c) the main witness had died, d) a provocation from people around. 2. The fact of making the conflict still incomplete because of there some people try to make the problem worse, while the village administration has tried to solve this case, such as : a) forgery geneology, b) any intervention from other side, c) threat from one of the conflict side, d) difficult to do the kinship mediation between the conflict people.[1] Kemenakan pendatang yang diangkat oleh kepala suku menjadi bagian dari sukunya[2] Salah satu suku yang ada di Minangkabau Sumatera Barat[3] Salah satu suku yang ada di Minangkabau Sumatera Barat